AN EXPLORATION OF ORTHOGRAPHIC CHALLENGES AMONG SEPEDI GRADE 10 LEARNERS IN ESSAY WRITING - Mashaphu, Ngoako Silas; Seanego, James (Universitas Islam Sumatera Utara (UISU), 2025)
Writing is a language skill that every Sepedi language custodian should master. Learners seem to encounter multiple orthographic challenges in their formal writing activities, thereby deviating from standard spelling rules in the language. This study aims to critically explore orthographic errors made by Sepedi learners in their essay writing. It is a qualitative study which seeks to assess the quality of language usage in Grade 10 classrooms. Four learners and two Sepedi educators were purposively sampled for this study. Learners’ formal activity scripts were utilized while teachers were interviewed to gather data, thereby employing document review and semi-structured interviews as data collection tools. Data were analysed thematically to identify and critically examine spelling challenges. Findings from this study indicate that learners face significant orthographic challenges, including differentiating between conjunctive and disjunctive writing systems, incorporating colloquial language into formal writing, and handling the insertion and omission of certain letters and vowels, as well as punctuation issues, among other issues. The study is expected to contribute to addressing overall orthographic challenges among Sepedi learners, as well as being handy to Sepedi language educators on how to instruct grammar lessons.